2021
DOI: 10.1186/s12917-021-02967-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment and integrated surveillance of foot-and-mouth disease outbreaks in Russia based on Monte Carlo simulation

Abstract: Background Foot-and-mouth disease (FMD) is a highly contagious disease of livestock worldwide. Russia is a big agricultural country with a wide geographical area where FMD outbreaks have become an obstacle for the development of the animal and animal products trade. In this study, we aimed to assess the export risk of FMD from Russia. Results After simulation by Monte Carlo, the results showed that the probability of cattle infected with FMD in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…They have become a hindrance in the trade of animal products and animals. In a study, it was concluded that the exported cattle of Russian origin have the risk of FMDV because of the presence of the infection in the region (66). In a study conducted on the prevalence of FMD in the last decade, it was reported that in Primosky Krai, the highest morbidity was seen in pigs, while in Amur Oblast, it was in cattle.…”
Section: Russiamentioning
confidence: 99%
“…They have become a hindrance in the trade of animal products and animals. In a study, it was concluded that the exported cattle of Russian origin have the risk of FMDV because of the presence of the infection in the region (66). In a study conducted on the prevalence of FMD in the last decade, it was reported that in Primosky Krai, the highest morbidity was seen in pigs, while in Amur Oblast, it was in cattle.…”
Section: Russiamentioning
confidence: 99%
“…[1]. In terms of assessment methods, many research methods, such as Monte Carlo simulation, the entropy method, fuzzy integrated evaluation, semiquantitative risk assessment techniques, entity-relationship models, and the construction of risk assessment index systems, have been explored and proposed [2][3][4][5][6][7][8]. Moreover, Vos et al compared and analyzed several generic risk assessment tools for animal disease transmission [9].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время ящур ликвидирован во многих странах, и ведется строгий контроль для предотвращения повторного заноса болезни в свободные от ящура регионы [7]. Страны, эндемичные по ящуру, имеют очень ограниченный экспортный рынок продуктов животноводства.…”
unclassified
“…Риск заноса ящура и меры его снижения. Вероятность завоза ящура из другой страны или региона определяется наличием в этом регионе хотя бы одного положительного случая в год [7]. Ключевые факторы риска заноса вируса -введение в стадо нового животного с неизвестным статусом вакцинации от ящура, сезонность, отсутствие вакцинации, размер стада.…”
unclassified